Insight Note Vol 3: Innovation Inventory 2021 - Schuetz, Tonya; Poulos, Allison; Sharkey, Rowan Olderman; Rubyogo, Jean Claude; Onyango, Patricia Atieno (2024)
The Bean Program & PABRA conducted an innovation inventory in 2021, collecting 47 innovations from 33 responses. The innovations were primarily products (57%), institutional arrangements (51%), and technologies (36%), distributed evenly across four development stages from discovery to implementation. Key beneficiaries include farmers (70%), national agricultural research systems (60%), policy advisors (57%), and private sector (57%). The survey revealed a healthy innovation pipeline with balanced distribution across development phases. Group discussions prioritized data quality and availability innovations, with most placed in "Birth, Maturity, and Renewal" ecocycle stages. The exercise successfully facilitated team discussions about priorities for the next 12-18 months. Challenges included limited session time and uneven ecocycle distribution, with only two innovations in the "creative destruction" phase. Recommendations include maintaining an open innovation survey year-round and holding dedicated innovation presentation sessions. 90% of participants rated the session highly successful.